FACILITIES FOR WATER RESOURCE SUPPLY IN ANCIENT ERSHI CITY (Scientific journal of the Fergana State University, 2025)
This article compiles information about the role of geographical factors in the emergence of the Marinskan population during historical periods. The hydrological factors influencing urban development are examined using examples from the early settlements in the Fergana Valley. The rhythmic changes of these factors or the reduction of their impact due to drought are studied. As a result of industrial development, the diminishing influence of natural factors on the creation of settlements leads to changes in their territorial distribution, which is explained using the example of the ancient city of Ershi in the valley.